Current account balance cyclicality - Afonso, António (2022)
We assess the cyclicality of current account balances for the period 2001Q1–2014Q4, focusing on Portugal and using Germany as a benchmark. We find that the cyclical component of the current account was positively explained by 3-month Euribor, but negatively by the financial crisis, systemic stress in Europe, employment and compensation of employees. Moreover, the noncyclical current account was positively affected by the period of the economic and financial adjustment programme and the terms of trade, but negatively influenced by financial integration.